2013
DOI: 10.1186/1746-4358-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Exclusive Breastfeeding Practices and associated factors among mothers in Bahir Dar city, Northwest Ethiopia: a community based cross-sectional study

Abstract: BackgroundBreastfeeding is an unequalled way of providing ideal food for the healthy growth and development of infants. World Health Organization (WHO) recommend exclusive breastfeeding (EBF) for six months which has a great contribution in reducing under five mortality, which otherwise leads to death of 88/1000 live birth yearly in Ethiopia. Hence, this study aimed to assess prevalence of EBF and associated factors in mothers in the city of Bahir Dar, Northwest Ethiopia.MethodsA community-based cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
133
7
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(199 citation statements)
references
References 17 publications
54
133
7
5
Order By: Relevance
“…Hence, without work or school constraints, they are able to provide breast milk as often as the child wants at any time of the day or night. In support of this, studies by Asma et al [22] and Seid et al [26] observed a decreased exclusive breastfeeding rate among working mothers and an association of exclusive breastfeeding with nursing mothers that were housewives respectively. On the contrary, Alemayehu et al [25] reported no association of exclusive breastfeeding with maternal employment.…”
Section: Discussionmentioning
confidence: 69%
“…Hence, without work or school constraints, they are able to provide breast milk as often as the child wants at any time of the day or night. In support of this, studies by Asma et al [22] and Seid et al [26] observed a decreased exclusive breastfeeding rate among working mothers and an association of exclusive breastfeeding with nursing mothers that were housewives respectively. On the contrary, Alemayehu et al [25] reported no association of exclusive breastfeeding with maternal employment.…”
Section: Discussionmentioning
confidence: 69%
“…Estes visam à promoção do aleitamento materno e incremento do conhecimento das mulheres durante a gestação 15,16 .…”
Section: Discussionunclassified
“…Webb-Girard et al 22 comentam que, entre as populações pobres, ainda persistem diferenças marcantes quanto ao acesso e qualidade da orientação alimentar e nutricional prestada pelos profissionais de saúde, em que as crianças são submetidas a regimes alimentares marcados pelo oferecimento precoce de alimentos complementares. Ademais, outros autores ressaltam a necessidade do trabalho materno fora de casa, devido à insegurança financeira, corroborando os resultados do presente artigo, o qual demonstrou maior risco de interrupção do AM sob livre demanda entre mães que trabalhavam fora do lar e que residiam na região metropolitana 15,19,20 .…”
Section: Discussionunclassified
“…The study conducted in Bahir Dar revealed that, Being a housewife, a young infant age, having a prenatal EBF plan, delivering at a health institution, delivering vaginally, receiving counseling, belief of breast milk sufficiency and maternal age of 18-23 were independently predictors of exclusive breastfeeding among mothers (30).…”
Section: Back Groundmentioning
confidence: 99%